A blind comparison of the effectiveness of endoscopic ultrasonography and endoscopy in staging early gastric cancer. Issue 3 (1st March 1999) - Yanai, H; Noguchi, T; Mizumachi, S; Tokiyama, H; Nakamura, H; Tada, M; Okita, K
Abstract : BACKGROUND/AIMS: Endoscopic ultrasonography is expected to be useful for invasion depth staging of early gastric cancer. A prospective blind study of the staging characteristics of endoscopy and endoscopic ultrasonography for early gastric cancer was performed. METHODS: Findings of endoscopy and endoscopic ultrasonography using a 20 MHz thin ultrasound probe were independently reviewed and the results of 52 early gastric cancer lesions analysed. RESULTS: The overall accuracy rates in invasion depth staging of early gastric cancer were 63% for endoscopy and 71% for endoscopic ultrasonography. No statistically significant differences were observed in overall accuracy. Endoscopic ultrasonography tended to overstage, and lesions that were classified as mucosal cancer by endoscopic ultrasonography were very likely (95%) to be limited to the mucosa on histological examination. All 16 lesions staged as mucosal cancer independently but coincidentally by both methods were histologically limited to the mucosa. CONCLUSIONS: Endoscopic ultrasonography is expected to compensate for the understaging of lesions with submucosal invasion that are endoscopically staged as mucosal cancer.